Do consumers pay the corporate tax? - Jacob, Martin; Müller, Maximilian A.; Wulff, Thorben (Contemporary Accounting Research, 2023)
Abstract Using granular gas price data and rich variation in corporate tax rates, we find that corporate taxes increase consumer prices. About 64% of the corporate tax is borne by consumers. The effect is stronger when firms have limited access to tax planning opportunities, face stricter tax enforcement, or when consumer demand is less elastic. Taxes also reduce the number of firms and their scale, consistent with a tax‐induced increase in marginal cost. Our results suggest that tax policies that increase effective corporate tax rates may have unintended consequences for consumers through higher prices.